If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5z + -1) + -5(z + 7) = 18(z + 1) Reorder the terms: 6(-1 + 5z) + -5(z + 7) = 18(z + 1) (-1 * 6 + 5z * 6) + -5(z + 7) = 18(z + 1) (-6 + 30z) + -5(z + 7) = 18(z + 1) Reorder the terms: -6 + 30z + -5(7 + z) = 18(z + 1) -6 + 30z + (7 * -5 + z * -5) = 18(z + 1) -6 + 30z + (-35 + -5z) = 18(z + 1) Reorder the terms: -6 + -35 + 30z + -5z = 18(z + 1) Combine like terms: -6 + -35 = -41 -41 + 30z + -5z = 18(z + 1) Combine like terms: 30z + -5z = 25z -41 + 25z = 18(z + 1) Reorder the terms: -41 + 25z = 18(1 + z) -41 + 25z = (1 * 18 + z * 18) -41 + 25z = (18 + 18z) Solving -41 + 25z = 18 + 18z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-18z' to each side of the equation. -41 + 25z + -18z = 18 + 18z + -18z Combine like terms: 25z + -18z = 7z -41 + 7z = 18 + 18z + -18z Combine like terms: 18z + -18z = 0 -41 + 7z = 18 + 0 -41 + 7z = 18 Add '41' to each side of the equation. -41 + 41 + 7z = 18 + 41 Combine like terms: -41 + 41 = 0 0 + 7z = 18 + 41 7z = 18 + 41 Combine like terms: 18 + 41 = 59 7z = 59 Divide each side by '7'. z = 8.428571429 Simplifying z = 8.428571429
| 3n-6=n+8 | | 3x-3=-3x-3 | | 4x^2+16x=48 | | 5x^2=3+3x | | x+15=55 | | n+8=3n-6 | | x+8=3n-6 | | 4x+2=6x-10 | | 25-X=12 | | 3(5z-1)-5(z+8)=2(z+1) | | 12k-3(5+5)=52 | | 2x+x=150 | | 2xm=18 | | 6(3z-1)-3(z+5)=10(z+1) | | 1.17x=140 | | 72y+-54+9y= | | 7t-3t+4t=-25 | | -36-3y+18=-21y+72+12y | | 0.01=2x-0.19 | | -98=-14x | | -2k=9 | | 6=x+9 | | 47=x-71 | | -4.9t^2+50t=0 | | -2+4.3=10.7 | | z+13=-3 | | 2(2x+3y)=0 | | 1.4(x+3.5y)+2(3.5x+1.7y)= | | (6x+2)2=4x+36 | | 5x+x=42 | | 5x+y=42 | | 80=2x^2+14x |